2014
DOI: 10.12793/tcp.2014.22.1.3
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A5*3Polymorphism and Its Clinical Implications and Pharmacokinetic Role

Abstract: The cytochrome P450 (CYP) 3A subfamily is estimated to participate in the biotransformation of 50% of the currently prescribed drugs. Four members of the CYP3A subfamily have been identified in humans: CYP3A4, CYP3A5, CYP3A7, and CYP3A43. Initial data suggested that CYP3A5 accounts for only a small proportion of the total hepatic CYP3A in about 20% of samples, but it was later revealed that CYP3A5 represents more than 50% of the total CYP3A amount in some individuals. Several genetic variants have been describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Concerning the rs776746 variant in CYP3A5, associations similar to those observed in our study have been reported, where high plasma levels are reported for drugs such as simvastatin, alprazolam, risperidone and carbamazepine [21][22][23][24][25][26] but not for imatinib. 27 Although there is already clear evidence of the effect of this variant on enzymatic activity due to a cryptic splicing site that causes a nonfunctional protein with decreased activity, the variant has also been associated with a puzzling and contradictory finding that shows greater elimination in patients who carry the variant than in patients with the normal allele.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Concerning the rs776746 variant in CYP3A5, associations similar to those observed in our study have been reported, where high plasma levels are reported for drugs such as simvastatin, alprazolam, risperidone and carbamazepine [21][22][23][24][25][26] but not for imatinib. 27 Although there is already clear evidence of the effect of this variant on enzymatic activity due to a cryptic splicing site that causes a nonfunctional protein with decreased activity, the variant has also been associated with a puzzling and contradictory finding that shows greater elimination in patients who carry the variant than in patients with the normal allele.…”
Section: Discussionsupporting
confidence: 90%
“…27 Although there is already clear evidence of the effect of this variant on enzymatic activity due to a cryptic splicing site that causes a nonfunctional protein with decreased activity, the variant has also been associated with a puzzling and contradictory finding that shows greater elimination in patients who carry the variant than in patients with the normal allele. 18,[25][26][27][28][29][30] In patients with the polymorphic allele, despite having a dysfunctional enzyme, the enzyme can have higher activity than that with the normal allele for some substrates of CYP3A5; however, the mechanisms are not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…A polymorphic variant can alter the metabolism or elimination of the cytotoxic agent; this could increase the plasmatic level of the antineoplastic, and therefore increase the risk of dose-related toxicity ( Lyman et al, 2014 ; Buaboonnam et al, 2019 ). Among these pharmacokinetics-related genetic factors, CYP3A4 and CYP3A5 are two enzymes that participate in the metabolism of most drugs used in the treatment of hematological malignancies ( Lee et al, 2013 ; Daly 2015 ), and polymorphic variants in the genes that encode those proteins are known to decrease their expression or functionality, decreasing drug metabolism ( Lamba et al, 2012 ; Park et al, 2014 ; Zhu et al, 2014 ). Moreover, polymorphic variants in genes that codify for drug transporters could affect the elimination of antineoplastic medications ( Choi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This mutation is present in the intronic lesion affecting alternative splicing, which leads to synthesis of a truncated and inactive CYP3A5 enzyme [10]. The frequency of the CYP3A5 expressor allele is known to be different among people of different ethnicity but is 76.5% for 6986A>G in Koreans [11–13]. Other than the CYP3A5 gene, various gene polymorphisms including ABCB1 , CYP3A4 , CYP2C8 , NR1I2 , PPP3CA , and PPP3CB were reported to correlate with tacrolimus metabolism trough levels [14].…”
Section: Introductionmentioning
confidence: 99%